2019
DOI: 10.1177/0340035219885145
|View full text |Cite
|
Sign up to set email alerts
|

From information, to data, to knowledge – Digital Scholarship Centers: An emerging transdisciplinary digital knowledge and research methods integrator in academic and research libraries

Abstract: In this essay, the authors will discuss the similarities and differences of knowledge management and librarianship. They will propose and articulate the emerging role of academic and research libraries as the integrators of digital knowledge and research methods among academic enterprises, a role which they believe will transform librarians to knowledge professionals. The authors will try to answer or stimulate further discussion of multi-dimensional and provocative questions such as: What are the critical dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…The analysis revealed that the two MT companies in Namibia comprehend KM, which centres around a process that stems from the belief that OK is inherently linked to enhancing employees' work understanding for improved performance, thereby managing it, contributing to the two MT companies' success, and providing a competitive edge. Becerra-Fernandez and Sabherwal (2015), Garcia-Perez et al, (2019), as well as Wang and Wang (2020), assert that the goals of KM are to improve an organisation's situational awareness and obtain a competitive advantage over its competitors. This perspective on the importance of managing OK has been further described by White (2004) and Becerra-Fernandez and Sabherwal (2015), who acknowledged that the broad scope of KM involves various tools and strategies to manage the OK of individuals, teams, and communities for an organisation's success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis revealed that the two MT companies in Namibia comprehend KM, which centres around a process that stems from the belief that OK is inherently linked to enhancing employees' work understanding for improved performance, thereby managing it, contributing to the two MT companies' success, and providing a competitive edge. Becerra-Fernandez and Sabherwal (2015), Garcia-Perez et al, (2019), as well as Wang and Wang (2020), assert that the goals of KM are to improve an organisation's situational awareness and obtain a competitive advantage over its competitors. This perspective on the importance of managing OK has been further described by White (2004) and Becerra-Fernandez and Sabherwal (2015), who acknowledged that the broad scope of KM involves various tools and strategies to manage the OK of individuals, teams, and communities for an organisation's success.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of KM for organisations has been emphasised in several reviews, including those by Jennex (2008), Bultrini and Newman (2020), Xiao (2020), Polas et al, (2021), and Mubuyaeta and Ngulube (2023). These reviews provide a clear rationale for implementing a KMS that incorporates the fundamental concepts of KM, as argued in the literature by Becerra-Fernandez and Sabherwal (2015), Garcia-Perez et al, (2019), andWang andWang (2020). A comprehensive understanding of KM and its concepts is crucial in designing and implementing an effective KMS for KM practice.…”
Section: Introductionmentioning
confidence: 99%
“…This approach helped the study to successfully focus on achieving its specific objectives, which are to comprehend the DSS needs of the users at VNU-HCM and to provide recommendations for the development of DSSs at VNU-HCM based on the identified needs. (Brenner, 2014;Craft, 2018;Hannah et al, 2020;Lippincott and Goldenberg-Hart, 2014;Mitchem and Rice, 2017;Smith et al, 2020;Tzoc and Millard, 2017;Wang and Wang, 2020;Zhifang and Huifang, 2018;Zhou et al, 2019) (S_18) Supporting the use of Geographic Information System (Zhou et al, 2019) (S_19) Website creation (Brenner, 2014;Craft, 2018;Mitchem and Rice, 2017) Provision of digital methods, tools, and information resources (S_20) Providing a venue for digital data processing (Zhifang and Huifang, 2018;Zhou et al, 2019) (S_21) Providing digital tools (Lippincott and Goldenberg-Hart, 2014;Zhifang and Huifang, 2018;Zhou et al, 2019) (S_22) Providing data storage space (Zhou et al, 2019) (S_23) Supporting the use of digital tools and methods in research (Kallaher and Gamble, 2017;Lippincott and Goldenberg-Hart, 2014;Wang and Wang, 2020;Zhifang and Huifang, 2018) (S_24) Supporting the use of digital tools and methods for teaching and learning (Zhifang and Huifang, 2018;Zhou et al, 2019) (S_25) Providing information resources (S_26) Supporting the use of copyrighted materials in research, teaching, and learning (Zhou et al, 2019) Digital sharing and publishing (S_27) Consulting/training/workshops on how to publish (Brenner, 2014;Craft, 2018;Hicks and Sinkinson, 2015;Zhou et al, 2019) (S_28) Assisting with publishing in institutional repositories …”
Section: Theoretical Frameworkmentioning
confidence: 99%